1989
DOI: 10.1111/j.1467-9787.1989.tb01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Firm Entry and Exit: Causality Tests and Economic‐base Linkages*

Abstract: One of the foundations of applied regional economics down through the years has been economic base theory (EBT). EBT presumes that economic activity within the basic sector unidirectionally causes economic activity in nonbasic sectors. In recent years, however, increasing attention has been given to the possibility that traditionally nonbasic activities (e.g., services) may be quite important in determining a region's total economic activity. In this paper, we examine the nature and direction of causality of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…' Richardson (1978: 92) criticized economic base models for the "one-way dependence of service industries on exports whereas the true relationship is of simultaneity and interdependence." In a study of firm entry and exit using vector autoregressive techniques, Mayo and Flynn (1989) reported a two-way relationship between manufacturing and nonmanufacturing firms. The effect from entry or exit of nonmanufacturing firms to subsequent entry or exit of manufacturing firms was small in magnitude, but statistically significant.…”
Section: Previous Studiesmentioning
confidence: 99%
“…' Richardson (1978: 92) criticized economic base models for the "one-way dependence of service industries on exports whereas the true relationship is of simultaneity and interdependence." In a study of firm entry and exit using vector autoregressive techniques, Mayo and Flynn (1989) reported a two-way relationship between manufacturing and nonmanufacturing firms. The effect from entry or exit of nonmanufacturing firms to subsequent entry or exit of manufacturing firms was small in magnitude, but statistically significant.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Given the urban hierarchy in the US., he concludes that growth of areas specializing in advanced services is linked to growth of areas specializing in production of final goods and services. In a recent study of firm entry and exits, Mayo and Flynn (1989) found a two-way causal relationship between manufacturing and nonmanufacturing firms in both rural and urban areas. While the magnitude of the causal effect from entry or exit of nonmanufacturing firms to subsequent entry or exit of manufacturing firms was small, it was statistically significant.…”
Section: The Decision To Exportmentioning
confidence: 99%
“…Empirical evidence has suggested a reexamination of the implied unidirectional association between basic and service-oriented sectors, particularly since industry linkages and regional adjustment mechanisms affect economic restructuring (Mayo and Flynn, 1989). Information on the degree to which transfer payments or a service-biased industry mix comprise a pseudo-economic base for a region is needed to assess real employment growth (Forward, 1982).…”
Section: Economic Base Theory and Estimationmentioning
confidence: 99%